2020
DOI: 10.3390/jcm9030648
|View full text |Cite
|
Sign up to set email alerts
|

Impact of New Chemotherapy Regimens on the Treatment Landscape and Survival of Locally Advanced and Metastatic Pancreatic Cancer Patients

Abstract: Background: New chemotherapy regimens for the treatment of metastatic pancreatic cancer have changed the therapy paradigm. We aimed to assess their impact on the treatment landscape and clinical outcome at our academic institution. Methods: In this single institutional posthoc registry analysis, we assessed characteristics and survival rates from all patients with locally advanced and metastatic pancreatic cancer who started a systemic treatment between 01/2011 and 12/2017. Survival analyses were performed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…2.2 ); this approximates the median OS seen in early-stage pancreatic patients managed with Whipple resection (≈ 16 months [ 49 ]). In Europe, Austrian investigators have attributed the improvement in survival benefit observed at their institution over time to changes in treatment patterns, in particular to the introduction of sequential therapy with first-line gemcitabine + nab-paclitaxel followed by second-line nal-IRI + 5-FU/LV [ 50 ]. Elsewhere in Europe, the efficacy of second-line nal-IRI + 5-FU/LV in patients with advanced PDAC following the failure of first-line gemcitabine + nab-paclitaxel is currently being evaluated as part of a phase III trial being conducted in Germany (PREDICT; NCT03468335).…”
Section: Place Of Liposomal Irinotecan In the Management Of Metastatimentioning
confidence: 99%
“…2.2 ); this approximates the median OS seen in early-stage pancreatic patients managed with Whipple resection (≈ 16 months [ 49 ]). In Europe, Austrian investigators have attributed the improvement in survival benefit observed at their institution over time to changes in treatment patterns, in particular to the introduction of sequential therapy with first-line gemcitabine + nab-paclitaxel followed by second-line nal-IRI + 5-FU/LV [ 50 ]. Elsewhere in Europe, the efficacy of second-line nal-IRI + 5-FU/LV in patients with advanced PDAC following the failure of first-line gemcitabine + nab-paclitaxel is currently being evaluated as part of a phase III trial being conducted in Germany (PREDICT; NCT03468335).…”
Section: Place Of Liposomal Irinotecan In the Management Of Metastatimentioning
confidence: 99%
“…Because of a lack of symptoms, patients are often diagnosed with PC at an advanced stage. Only a few patients have an opportunity for surgical resection, which makes chemotherapy an important component in the systemic treatment of PC [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Radical surgery, including vascular reconstruction, has been reported as technically feasible, expanding surgical indications for PDAC [2]. Moreover, recent studies showed that patients with borderline resectable (BRPC) or locally advanced pancreatic cancer (LAPC) who underwent surgery after neoadjuvant chemotherapy (NACT) had better survival outcomes than those who underwent upfront surgery [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%